2020
DOI: 10.3892/etm.2020.9298
|View full text |Cite
|
Sign up to set email alerts
|

Observation of hemodynamic parameters using a non-invasive cardiac output monitor system to identify predictive indicators for post-spinal anesthesia hypotension in parturients undergoing cesarean section

Abstract: The administration of high-level spinal anesthesia for cesarean section may lead to significant hemodynamic changes. Bioreactance-based non-invasive cardiac output monitoring (NICOM™) provides an accurate monitoring system for parturients under spinal anesthesia. The present study hypothesized that baseline hemodynamic parameters obtained via the NICOM™ system could serve as predictive indicators for post-spinal anesthesia hypotension. Therefore, 80 full-term parturients with singleton pregnancies who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…They also found cardiac output increased in the 15° left operating table tilt. However, no such result was observed in the study of Yeh et al 30 The reason for this result might be a change in hemodynamic status caused by preperfusion of 750 mL 0.9% saline fluid.…”
Section: Discussionmentioning
confidence: 83%
“…They also found cardiac output increased in the 15° left operating table tilt. However, no such result was observed in the study of Yeh et al 30 The reason for this result might be a change in hemodynamic status caused by preperfusion of 750 mL 0.9% saline fluid.…”
Section: Discussionmentioning
confidence: 83%
“…Compared to the parturients without SAIH, those with SAIH had a significantly lower baseline SBP (122 [interquartile range = 114-130] vs 130 [120-143] mmHg, p < 0.001), heavier large fetal weight (3098 [2742-3345] vs 2930 [2576-3266] g, p < 0.001), were more often multiparous (259 [60.4%] vs 261 [45.8%], p < 0.001), had a higher percent change in lowest SBP (33 [27-39] vs 19 [12][13][14][15][16][17][18][19][20][21][22][23][24][25]%, p < 0.001), and shorter time to lowest SBP after spinal anesthesia (14.9 [10][11][12][13][14][15][16][17][18][19][20] vs 15.9 [10][11][12][13][14][15][16][17][18][19][20] minutes, p < 0.001).…”
Section: Univariate Analysis Of Saihmentioning
confidence: 99%
“…12,13 In a systematic review, 13 Yu et al classified the predictive factors of post-spinal anesthesia-induced hypotension (SAIH) into seven domains: demographic characteristics, baseline hemodynamic parameters, sympathovagal balance indices, postural stress testing, peripheral perfusion indices, blood volume and fluid responsiveness indices, and genetic polymorphisms. Most previous studies have focused on demographic characteristics such as maternal weight and body mass index (BMI) [14][15][16] and baseline hemodynamic parameters such as baseline heart rate (HR) 15 and baseline systolic blood pressure (SBP) [17][18][19] to predict post-SAIH, however the results have been inconclusive. Therefore, we conducted this retrospective study to investigate the factors associated with the need for higher doses of vasopressors in women undergoing cesarean section.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, only three reported a weak relationship between maternal weight and body mass index (BMI) with spinal anesthesia-induced hypotension. 19,25,26 Many more studies found no predictive value of BMI, maternal weight, height, or body roundness index. 5,11,14,16,18,21,[27][28][29] Ghabach et al 30 reported that maternal weight gain during pregnancy was valuable in predicting spinal anesthesia-induced hypotension, however the sensitivity was low (53.1%).…”
Section: Domain I Demographic Characteristicsmentioning
confidence: 99%
“…However, the predictive value of PVI in two studies was moderate (AUROC 0.6 and 0.75) (Supplementary Table 7), 28,38 and in three additional studies the PVI was not predictive of spinal anesthesia-induced hypotension. 17,19,23 Baseline cardiac output index, stroke volume (SV) 26 and cardiac output change during passive leg raise (PLR) test 12 were also not good predictors.…”
Section: Domain VI Blood Volume and Fluid Responsiveness Indicesmentioning
confidence: 99%